2019
DOI: 10.2147/imcrj.s200201
|View full text |Cite
|
Sign up to set email alerts
|

<p>Suspected hyponatremia-induced Brugada phenocopy</p>

Abstract: Brugada syndrome is a genetic condition that predisposes to an increased risk of ventricular fibrillation and sudden cardiac death in a structurally normal heart. The Brugada type 1 electrocardiogram (ECG) pattern may occur independently of the actual syndrome, and this clinical phenomenon is often referred to as Brugada phenocopy. There are several other factors which have been known to induce this electrocardiographic pattern, and currently, there is a paucity of literature with respect to the pattern that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(42 reference statements)
0
8
0
Order By: Relevance
“… 5 The Brugada phenocopy with severe hyponatremia alone has not been well documented with only a few case reports found. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 The Brugada phenocopy with severe hyponatremia alone has not been well documented with only a few case reports found. 7 …”
Section: Discussionmentioning
confidence: 99%
“…A combination of hyponatremia and hyperkalemia attributed to underlying primary adrenal insufficiency were likely responsible for the Brugada phenocopy on initial ECG at presentation, and syncope was likely an orthostatic or vasovagal event. 6 , 7 Resolution of dynamic ECG changes with electrolyte correction suggests against the Brugada syndrome and represents the Brugada phenocopy.…”
Section: Discussionmentioning
confidence: 99%
“…Fever was found to be the precipitating factor of cardiac arrest in 18% of Brugada syndrome arrests [ 6 ]. Another potential trigger is electrolyte disturbances such as hyperkalemia and hyponatremia [ 7 ]; hyponatremia has been reported in the literature as a rare trigger for the Brugada pattern [ 8 ]. It is suspected that severe hyponatremia diminishes the electrochemical ionic gradient by decreasing the inward sodium current and leaving the transient outward current unopposed [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drugs of abuse such as cannabinoids, heroin, and cocaine have been associated with BrP [14]. Changes in the ECG secondary to heroin such as QTc prolongation, torsades de pointes, and bradyarrhythmia are also well documented [15]. Ramsaroop et al described a patient who required Naloxone to be resuscitated with positive toxicology screen for alcohol and opiates [15].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the ECG secondary to heroin such as QTc prolongation, torsades de pointes, and bradyarrhythmia are also well documented [15]. Ramsaroop et al described a patient who required Naloxone to be resuscitated with positive toxicology screen for alcohol and opiates [15]. Ghovanloo et al demonstrated that cannabinoids have a potential inhibitory effect on sodium channels under certain circumstances [16].…”
Section: Discussionmentioning
confidence: 99%